The ontological foundation for studying the future. Issue 5 (28th July 2020) - Clardy, Alan
Abstract : Purpose: The purpose of this paper is to develop an ontological foundation for future studies, based in part on integrating some prior albeit incomplete work in this area. Design/methodology/approach: This manuscript is based on a literature review, as well as on conceptual and theoretical enhancements from this subject field. Findings: As the future does not exist (it is always something yet to come), the ontological foundations for studying the future must be based on the current reality of the physical, biological and social-psychological worlds of experience and ideas. From this basis, 10 postulates are provided that are based on that current reality and are applied to studying the future. Thus, by characterizing the current reality and how it is understood by people, meaningful statements about the future are possible. Practical implications: For each ontological postulate, one or more implications for the study of the future are provided as guidelines for practice. Originality/value: This manuscript integrates and builds on prior offerings about ontological concerns into a comprehensive framework that legitimates and focuses the practices of studying the future.